2020
DOI: 10.1186/s12876-020-01417-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of gastroesophageal reflux disease in Iran: a systematic review and meta-analysis

Abstract: Background Gastroesophageal reflux disease (GERD), which leads to acid reflux into the esophagus, is a common gastrointestinal disorder. Several studies have shown the prevalence of GERD in Iranian population, but their evidence is contradictory. Therefore, the present study was conducted to investigate the epidemiology of GERD in Iran. Methods The entire steps of this systematic review and meta-analysis were based on the MOOSE protocol, and the results were reported accordance with the PRISMA guideline. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…43 A systematic review and meta-analysis study in Iranian population the daily, weekly, monthly, and overall prevalence of GERD symptoms was 5.64%, 12.50%, 18.62% and 43.07%, respectively. 44 The present meta-analysis has many strengths. We utilized a universal and repeated search to increase the ability to detect all related papers.…”
Section: Discussionmentioning
confidence: 99%
“…43 A systematic review and meta-analysis study in Iranian population the daily, weekly, monthly, and overall prevalence of GERD symptoms was 5.64%, 12.50%, 18.62% and 43.07%, respectively. 44 The present meta-analysis has many strengths. We utilized a universal and repeated search to increase the ability to detect all related papers.…”
Section: Discussionmentioning
confidence: 99%
“…GERD is known as another important risk factor for esophageal cancer which is associated with obesity as well [9]. A systematic review and meta-analysis conducted in Iran have shown that the overall prevalence of GERD in the Iranian population was about 40%, so it is an important risk factor to take into account [20]. Also, it was shown that the daily symptoms of GERD were significantly higher in females [20].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis conducted in Iran have shown that the overall prevalence of GERD in the Iranian population was about 40%, so it is an important risk factor to take into account [20]. Also, it was shown that the daily symptoms of GERD were significantly higher in females [20]. Furthermore, obesity and smoking were known as possible risk factors for developing Barret's esophagus in GERD [21].…”
Section: Discussionmentioning
confidence: 99%
“…Gastroesophageal Re ux Disease (GERD) is a common gastrointestinal disorder that adversely affects the patients' quality of life (1)(2)(3). Considering wide use of over-the-counter medications and diagnostic procedures, it imposes a huge economic burden on the healthcare system (4).…”
Section: Introductionmentioning
confidence: 99%